Las nuevas transmisiones de narrativas indígenas en manuales educativos: escuela y resiliencia social-ecológica de pueblos indígenas amazónicos - Yoza-Mitsuishi, Katia (Mundo Amazónico, 2024)
Amazonian studies in Peru have traditionally focused on anthropological and linguistic issues, often neglecting the question of resilience, particularly in the context of indigenous education and its transmission traditional narratives. This article aims to highlight the role of school in fostering socio-ecological resilience by analyzing the manual Lo que nos pertenece. Patrimonios culturales de los pueblos amazónicos from Formabiap (the Intercultural Bilingual Education Training Center of the Peruvian Amazon), which operates under the interference of the AIDESEP (Inter-ethnic Association for the Development of the Peruvian Jungle). Drawing on contemporary theory and criticism, I argue that the manual introduces new ways of transmitting narratives and traditional knowledge to younger generations, emphasizing humansnon-humans alliances as a strategy for the self-determination and promoting “Buen vivir” as an alternative to conventional development. Formabiap ’s educational vision, as well as the discourses presented in its manuals, promote Amazonian resilience by fostering critical thinking and a shared Amazonian indigenous identity across various peoples. In conclusion, Formabiap implements AIDESEP's political agenda for indigenous self-determination in education, making the study of its manuals central not only to pedagogy but also to understanding contemporary Amazonian resilience.